The Increasing of Body Mass Index and The Pes Cavus have a higher prevalence of the Plantar Fasciitis In the Elderly - Indah Margaretha Masela; Titi Moertolo; Kirana Anggraeni (Indonesian Journal of Physical Medicine & Rehabilitation, 2017)
Introduction : The Plantar fasciitis (PF) is an increasing degenerative process of the plantar fascia in elderly.The study has proven that PF has related to the body mass index (BMI) and the foot posture. The study aimedwas to identify the relationship between the BMI and the foot posture, with the incidence of PF in the elderlythat lived in a nursery home.Method : The design study was the cross-sectional. A footprint assessed the foot posture. The BMI was measuredby divided the body weight (Kg) with the body height square (M2 ). The foot posture was examined by footprint by ink on a papper. The degree of plantar fasciitis assessed by the score of the Foot Function Index (FFI).Statistical analysis was univariate and bivariate analysis by the Kruskal-Wallis test.Result : There was a correlation between the BMI and the plantar fasciitis (p=0,029). However, there was nocorrelation between the foot posture and plantar fasciitis (p=0,280). Otherwise the foot posture of pes cavus hasthe highest of the FFI score (60.92).Discusion :The increasing of BMI has the higher prevalence of the plantar fasciitis in the elderly. Furthermore,the foot posture of Pes cavus has a higher prevalence in plantar fasciitis among foot postures.Keywords : Pes planus, pes cavus, body mass index, plantar fasciitis, elderly.